OS3.5 Dynamic insights into the cellular heterogeneity of malignant gliomas. (19th September 2018) - Xie, R; Kessler, T; Grosch, J; Huang, L; Solecki, G; Wick, W; Winkler, F
Abstract: Background: Glioblastoma is the most frequent primary malignant brain tumor characterized by poor survival due to its high resistance to standard therapies. Intra- and intertumoral heterogeneity has been described on many levels. We have recently found that astrocytomas, including glioblastomas, extend tumor microtubes (TMs) to colonize the brain, and allow for long-distance interactions between tumor cells; however, they are heterogeneously formed in the tumor, with about half of the cells staying unconnected. The TM-connected glioma cells resist the adverse effects of radio- and chemotherapy, and repair surgical lesions, being the resistant backbone of the disease. Thus, an important but yet unresolved question is how TM-connected tumor cells differ from the rest. Moreover, it remained unclear, whether cellular heterogeneity in glioblastoma is either plastic or fixed. Material and Methods: We identified sulforhodamine (SR) 101 to specifically label astrocytes and astrocyte-connected glioblastoma cells, and SR101 was injected into mouse model carrying cranial window to distinguish TM-connected vs. TM-unconnected cells in vivo . Both glioblastoma cell subpopulations were separated ex vivo by FACS sorting, and analyzed with high-throughput RNA sequencing. Immunostaining of tumor sections from patients and xenografts was performed to identify stem cell markers, and correlated with TMs. In vivo reporter system based on GFP expression driven by nestin responsive promoter element was applied to dynamically monitor TMs and molecular changes during tumor progression and therapy responses. Results: TM-connected glioma cells with high uptake of SR101 showed gene expression profiles compatible with astrocytic character, cellular stemness, cellular proliferation, and ingenuity profiles enriched for genes involved in cell-to-cell interaction and tissue development. Those cells were particularly nestin-rich, an established marker for glioma cell stemness. Nestin expression as measured with the in vivo reporter system was very high under stem-like in vitro conditions, and decreased over time after tumor implantation, with only a small subpopulation remaining nestin-positive in established gliomas. Nestin expression was up-regulated under stress, and highly correlated with TM-connectivity, TM-proficiency and cellular resistance. Ex vivo experiment revealed that nestin+ population displayed higher sphere formation ability than nestin- cells. Tumor formation assays after re-implantation of connected vs. unconnected cells are ongoing, as well as single cell RNA-Seq analysis. Conclusion: Stem-like cellular features are enriched in TM-connected glioma cells, and strongly correlated with the progression and therapy resistance of gliomas. Glioma cells can dynamically change their cellular identity over many days, particularly after stress.